2013
DOI: 10.1787/5jzbcx0czc0x-en
|View full text |Cite
|
Sign up to set email alerts
|

Home Sweet Home: The Determinants of Residential Satisfaction and its Relation with Well-being

Abstract: JT03350773Complete document available on OLIS in its original format This document and any map included herein are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…To construct and implement an efficient housing policy, it is crucial to understand the determinants that define and control occupants' satisfaction with their living conditions. Balestra and Sultan (2013) found that there is a complex relationship between residential satisfaction and housing characteristics, including the neighborhood's features. This study has emphasized that housing is considered a right for everyone, and the main objective of any housing program is to upgrade the liveability conditions and guarantee fair access to satisfactory and adequate housing to meet the needs of users.…”
Section: Literature Review 21 Determinants Of Residential Satisfactionmentioning
confidence: 99%
“…To construct and implement an efficient housing policy, it is crucial to understand the determinants that define and control occupants' satisfaction with their living conditions. Balestra and Sultan (2013) found that there is a complex relationship between residential satisfaction and housing characteristics, including the neighborhood's features. This study has emphasized that housing is considered a right for everyone, and the main objective of any housing program is to upgrade the liveability conditions and guarantee fair access to satisfactory and adequate housing to meet the needs of users.…”
Section: Literature Review 21 Determinants Of Residential Satisfactionmentioning
confidence: 99%
“…According to Lee (2014), the settlement environment and rural environment affect life satisfaction; but at the same time, poor living conditions can threaten public welfare, and as a main cause of the depopulation of villages, can also reveal the types of solutions required to alleviate it [14]. According to scholars, environmental quality of life domains include satisfaction with housing, schools, health services, safety and security, roads, and access to transport [15][16][17][18]. In a rural study by Chow (2005) on assessing the degree of satisfaction degree with different aspects of life, respondents were most satisfied with living conditions and living arrangements [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Digital resources in the classroom can serve as an equalising force between students who do and do not have access to digital technologies at home, allowing the latter to catch up with the digital mastery of the former. In addition, Banerjee et al (2007) suggest that computer-assisted learning especially benefits schools where the quality of teaching is lower, meaning that differences in teacher quality across schools can partially be mitigated by the introduction of digital resources in the classroom.…”
Section: Digital Resources In Classrooms Can Help Prepare Students Fomentioning
confidence: 99%
“…Housing is important for well-being to meet basic human needs such as shelter from bad weather and to provide people with security and privacy. In addition, poor housing conditions, whether due to overcrowding or in the form of health hazards due to poor building standards, can be detrimental for people's health and mental well-being (Balestra and Sultan, 2013). The digital transformation can do little to improve or detract from the function of housing in facilitating these needs.…”
Section: Housingmentioning
confidence: 99%